Working Together for a Common Goal: The International Armed Forces Community Nursing Research Collaboration - Stephen McGhee; Deborah Kenny; Alicia Rossiter; Katherine Ling; Susan Sheehy; Linda H. Yoder; William T. Bester; Kelly Wolgast; Alan Finnegan (The Ohio State University Libraries, 2023)
Over the past 19 years, millions of military service members from the United States (U.S.) and United Kingdom (U.K.) served alongside each other in Iraq and Afghanistan. The U.S. and U.K. clearly recognize the sacrifices that the members of their armed forces have made for their respective countries. Sir Winston Churchill described the special relationship which has facilitated cooperation between the U.S. and U.K. in economic activities (trade and commerce), intelligence sharing, and the planning and execution of military operations and military medicine. It would be to the benefit of all, especially the military members, veterans, and family members, if nursing also joined in this collaborative effort. Ensuring the efforts of NATO nurse scientists and educators working to advance military, veteran, and their families' health are aligned requires outlining key priorities across nations and identifying resources that can facilitate collaborations. To that end, with the support of the American Academy of Nursing (AAN), the International Armed Forces Community Nursing Research Collaboration (IAFNRC) was established. This manuscript provides detailed insight into the work of the IAFNRC.